2006
DOI: 10.1002/dvdy.20836
|View full text |Cite
|
Sign up to set email alerts
|

Bmp2 and Gata4 function additively to rescue heart tube development in the absence of retinoids

Abstract: We used the vitamin A-deficient (VAD) quail model to investigate the retinoid-dependent mechanism that regulates heart tube development. We showed previously that decreased levels of Gata4 in cardiogenic mesoderm and endoderm correlate with the cardiomyopathy caused by VAD, but that this could be rescued by transplanting normal anterior endoderm. Bmp2 is a known cardiogenic factor that is expressed normally in lateral plate mesoderm and cardiac-associated pharyngeal endoderm. Here we show that (like Gata4) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Whether this interference contributes to HPV-related pathogenesis is unclear, yet it may offer novel treatment options. A common feature of the 5 methylation signature genes identified in our study is their involvement in tissue development and regeneration, and 4 of them, ALDH1A2, OSR2, GATA4, and IRX4, are related to retinoid metabolism and signaling (25,26,(68)(69)(70)(71)(72)(73)(74). Since retinoic acids exert potent effects on cell growth, differentiation, and apoptosis, targeting one or a combination of the 4 genes and thereby modulating retinoid metabolism and signaling may offer novel avenues in successful treatment of OPSCC (75,76).…”
Section: Discussionmentioning
confidence: 73%
“…Whether this interference contributes to HPV-related pathogenesis is unclear, yet it may offer novel treatment options. A common feature of the 5 methylation signature genes identified in our study is their involvement in tissue development and regeneration, and 4 of them, ALDH1A2, OSR2, GATA4, and IRX4, are related to retinoid metabolism and signaling (25,26,(68)(69)(70)(71)(72)(73)(74). Since retinoic acids exert potent effects on cell growth, differentiation, and apoptosis, targeting one or a combination of the 4 genes and thereby modulating retinoid metabolism and signaling may offer novel avenues in successful treatment of OPSCC (75,76).…”
Section: Discussionmentioning
confidence: 73%
“…More likely it is the feedback repression that Nkx2.5 normally imposes on Bmp2/ Smad signaling (31), which when relieved may improve the RA deficiency phenotype. Transplantation of W T foregut endoderm, or exogenous supply of BMP2 and Gata4, can restore heart morphology in vitamin A-deficient quail embryos (35,36). Although Bmp2 expression indeed appears up-regulated in Nkx2.5;Raldh2 compound mutants, further genetic strategies are required to clarify the precise manner by which these two signaling pathways interact.…”
Section: Discussionmentioning
confidence: 99%
“…Gata4 is expressed most strongly at the 5 somite stage in the region of the presumptive inflow tract and posterior heart tube, and this is precisely the region that fails to develop normally in the VAD embryo. Studies showed that VAD results in reduced expression of Bmp2 throughout the sino-atrial region [59]. Furthermore, addition of exogenous Bmp2 can function additively with forced expression of Gata4 to overcome the loss of retinoid signaling, indicating the presence of an active RA-BMP-GATA network for posterior heart tube development.…”
Section: Retinoic Acid and Early Heart Developmentmentioning
confidence: 99%